2010
DOI: 10.1016/j.ejso.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in use of immediate breast reconstruction after mastectomy for breast cancer in England

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 7 publications
2
56
0
1
Order By: Relevance
“…This compares favourably with rates of 16–59 per cent internationally3 8, 19 27, 28, 29, 30. The strongest predictors of PMBR cited were: age under 50 years; white race; higher income and education; and earlier disease stage31.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This compares favourably with rates of 16–59 per cent internationally3 8, 19 27, 28, 29, 30. The strongest predictors of PMBR cited were: age under 50 years; white race; higher income and education; and earlier disease stage31.…”
Section: Discussionmentioning
confidence: 77%
“…Recent guidelines5 6 recommend that reconstruction should be discussed and offered as an option for the majority of women undergoing mastectomy. Postmastectomy breast reconstruction (PMBR) has thus been incorporated into the contemporary surgical management of patients with breast cancer, resulting in increasing reconstruction rates, as reported in national audits of populations in both the UK and USA7 8.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,16,17,18,[20][21][22][23][24][25][26][27][28]30 This is in part because of concern about increased complication rates with age and comorbidities. In an attempt to identify predictors of breast reconstruction using the hospitalbased national sample of inpatients from 1999-2003, Reuben and colleagues 27 found that the association between age and breast reconstruction remained significant after controlling for comorbidities.…”
Section: Agementioning
confidence: 99%
“…13,19 We identified six studies from other jurisdictions, four of which were English-language publications (Table 3). [28][29][30][31] Australia, Denmark and England reported national rates of breast reconstruction of 9.9% (1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000), 14% (1999-2006) and 16.5% (2006-2009), respectively. [28][29][30] A study from a single institution in Shanghai, China, reported an increase in the rate of reconstruction from 1.3% in 1990 to 5.1% in 2005.…”
Section: How Often Is Breast Reconstruction Performed After Mastectomy?mentioning
confidence: 99%
See 1 more Smart Citation